Le droit au service du syndicalisme. Les juristes de la CFDT - Cécile Guillaume; Jean-Michel Denis (La Nouvelle Revue du Travail, 2020)
Driven by the demands of their members and the legalization of employment relations, trade unions have engaged in processes of internalization of the law in the form of internal legal services. The legal professionals employed in those services have to work in organizations where forms of political rationality predominate and may conflict with the professional logic they represent. This article examines the conditions under which they exercise their profession between expert knowledge and militant logic and questions the hybrid professionalization process they manage to build.